Efek Regulasi Emosi Terhadap Motivasi Belajar: Studi Analisis Kasus Berdasrkan Letak Geografis Daerah Asal Mahasiswa Universitas Terbuka: Effect Regulation Emotion To Motivation Study: Study Analysis Case Based on Location Geographical Area of Origin Universitas Terbuka Students - Apri Kasman (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
This research aims to analyze the influence of emotional regulation on the learning motivation of Open University (UT) students, by considering the geographic location of the student's home area as a moderating variable. Emotional regulation is an important factor in the learning process, because it can influence the way students face challenges and pressure in their studies. Learning motivation, on the other hand, plays a vital role in student academic achievement. This research uses quantitative methods with a case analysis design, involving 400 Open University students from various regions in Indonesia. Data was collected using a questionnaire that measures the level of emotional regulation and learning motivation, as well as geographical variables that influence students' learning conditions. The research results show that emotional regulation has a positive effect on learning motivation, with significant differences between students from urban and rural areas. Students from urban areas tend to have better emotional regulation, which results in higher learning motivation compared to students from rural areas. These findings provide new insights for the development of more effective learning strategies in distance education environments, taking into account students' psychological and geographical aspects.